Sistem Informasi Operasional dan Pemeliharaan Bangunan Sungai Berbasis Web : Studi Kasus pada Pada Balai Besar Wilayah Sungai Sumatera VIII - Muhammad Rezky Alfarobi; Baibul Tujni (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
Balai Besar Sungai Sumatra VIII is in charge of managing water resources in river areas, which includes planning, implementing construction, operation and maintenance in the framework of conservation and utilization of water resources and controlling the destructive power of water in rivers, lakes, reservoirs, dams and other water reservoirs, irrigation, groundwater, raw water, swamps, ponds and beaches to support activities in operation and maintenance, inventory and monitoring of river structures, both newly built and those that are no longer functioning, are carried out. In this case, a third-party consultant conducts field inspections and analyzes the building and the surrounding area. The results of the reports submitted by the contractor in the form of report documents and Excel files in the assessment of inspection results from these results will be decided using criteria to determine the results of the decision to make improvements. The results of the submitted reports have not been managed digitally, so to look for report data carried out in the previous year, you have to search on a computer. It takes quite a long time, and there is a possibility that the data cannot be found. The results of the reports submitted by the contractor are in the form of document reports and Excel files in the assessment inspection results; these results will be decided using the criteria to determine the results of the decision to make improvements, encourage the author to develop a system that can inventory and maintain river buildings, which can minimize document collisions and make it easy to find the required data. Web-based and using the MySQL database to accommodate these activities so that it can make it easier to search and minimize piles of documents.